Para crítica ao campo dos determinantes sociais da saúde - Garbois, Júlia Arêas (2014)
This study analyzes the relationship between 'health' and 'social' in the Brazilian Public Health, specifically the notion of 'social determinants of health', focusing on two important moments: the 70's, when the construction of this notion occurred from the medical and social Latin American chain, and the resumption of this discussion in the XXI century, over the seal of 'social determinants of health'. It possessed the following objectives: characterize the notion of 'social determinants' from positivism in the social sciences, search the construction of the notion of 'social determinants of health' in the Brazilian Public Health; describe perspectives analysis on the field of social determinants of health from the polarity between 'health' and 'social'. To achieve the objectives, an exploratory study was conducted through literature (books and virtual databases) and documentary research. Initially we present the theoretical and philosophical assumptions upon which modern science was settled and that built the foundation of positivist current. After, we characterized, in general, this line of thought, to finally interpret the notion of 'social determinants' from Durkheim - one of the main analyzes within the field of social sciences. Soon after, we bring the construction of the concept of social determinants of health from the Latin American criticism of the 70s to the hegemonic discourse of the period on the health-disease process. The Latin American thought had great production in Brazilian’s theoretical and policy at the forefront when compared to all the countries of South and Central America. Among other agendas, the notion of social determinants of health, arising from social movements, guided the Brazilian health reform, placing itself as the heart of the debate. This notion sustained the 'political banner' advocated by health movement in the struggle for better living conditions and health in Brazil. Then, we present the latest scientific-political configuration of the field of social determinants of health, emphasizing a predominantly reductionist focus on the social occurs. Soon after, we bring the categories of the thought of critical’s sociology and contemporary’s sociology in order to provide elements of analysis to the critique of how hegemonic discourse has been guided within the field of social determinants of health. Both perspectives are presented in a non-exclusive, non-hierarchical and non-competitive way. We end with considerations that, far from being final, point to the need for a new perspective from which to current studies in the field of social determinants of health.